A review of the Infectious Bursal Disease (IBD) in Iran - Salavati, Ali; Peighambari, Seyed Mostafa (Journal of Poultry Sciences and Avian Diseases, 2023)
Infectious bursal disease (IBD) is one of the most important diseases in the poultry industry all over the world. It is a viral disease caused by a birnavirus, which weakens the immune system. The disease was observed for the first time in 1962 in the Gumboro area of ​​Delaware, USA. The first report of this disease in Iran dates back to 1994. Since then, various investigations have been conducted in Iran on the isolation and identification of IBDV isolates, cognitive immunological studies and vaccine testing and design, disease pathogenesis and pathology, and recently in the field of genetic engineering. The main procedure for IBD control is vaccination in productive and commercial herds. Therefore, studies related to vaccination and immunogenicity play an essential role in designing preventive measures against this disease. In this manuscript, a comprehensive review of the studies conducted in Iran on IBD has been discussed.